IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DI KABUPATEN WONOSOBO TAHUN 2015 - 2107 - Fachrudin, Muhammad Arif; Taufiq, Achmad; Astuti, Puji (Journal of Politic and Government Studies, 2018)
Abstract. Poverty is a humanity problem that inhibits welfare and civilization and is a problem that must and can be solved. Poverty alleviation is currently still material-oriented so that the sustainability of this alleviation is highly dependent on the budget availability and government commitment. The poverty reduction program in Indonesia that is not just material-oriented is the Family Expectency Program. The implementation of PKH is expected to improve the socio-economic, educational, and public health, especially for the poor. The purpose of this study is to describe the implementation of PKH, the form of the program of PKH, and to find the supporting and inhibiting factors and solutions to solve the problem of poverty in Wonosobo District.The theoretical approach used in this research is the approach model of policy implementation George Edward III. The theory takes four main variables for effective policy implementation ie communication, resources, disposition, and bureaucratic structure. The research method used in this research is the method of mix (mix method) with qualitative as the main approach and data collecting techniques such as observation, interview, kuesione, and document studies. The informants in this study were divided into two categories, The first is Category 1 that consists of The Informants who have access and high intensity to PKH, the key figures who know more information in the implementation of Family Expectency Program (PKH), namely The Head of Si (Kasi) Protection and Social Welfare Warranty Department of Community and Village Empowerment of Wonosobo Regency, Coordinator of PKH Regency of Wonosobo Regency, and Assistant PKH of Wonosobo Regency. The Second Category, Category II consists of The community beneficiaries of the Family Hope Program  in Wonosobo District, especially that are in the four sample districts (Garung, Kalikajar, Kertek, and Kepil Subdistricts) in total 100 samples of KPM. For the second category of informants, the questions to be asked are using the research questionnaire The results of the study show that the Implementation of Family Expectency Program in Wonosobo District in 2015 - 2017 covers several processes and stages consist of planning, socialization, data collection, mentoring, and distribution of assistance. In practice, there are still technical constraints. The data of PKH participants has not been comprehensive, so there are still some people who have not got PKH yet. The number of KPM is still not comparable with the number of available companion so that the companion is still overload and should be added again. For long term, PKH needs commitment and support from all parts so that this program can run so well to reduce the burden of poverty in Wonosobo.              Keywords : Policy Implementation, Family Expectency Program